2./ 8. asır vâsıt hadis halkaları - Rahmet Demireşik, Rukiyye (My University, 2025)
2./ 8. asır vâsıt hadis halkaları 1./ 7. asır sonlarında Irak Valisi Haccâc b. Yusuf tarafından, dönemin iki büyük ilim merkezi olan Basra ve Kûfe arasına, jeopolitik önemi gözetilerek bir garnizon şehri olarak kurulan Vâsıt, özgün nitelikleriyle erken İslam tarihi açısından dikkat çekici sorulara kapı aralar. 2./ 8. asırda Vâsıt’ın hadis ilmi açısından taşıdığı önemi ve konumunu tespit edebilmek için şehrin siyasi, sosyal ve ekonomik şartları dikkate alınmalıdır. Zira bu şehirde doğanlar, doğrudan sahabe neslinden hadis öğrenme imkânına sahip değildir; onların dönemin ilmî hareketliliğine eklemlenme süreci, şehrin özgün yapısı içinde gelişmiştir. Bu bağlamda şu sorular önem kazanmaktadır: Vâsıt, 2./ 8. asırda orada yaşayan hadis râvilerine nasıl bir ilmî zemin sunuyordu? Bu zemin, halkaların oluşum süreçlerini nasıl etkiledi ve hangi yönleri sebebiyle Vâsıt önde gelen ilim merkezleri arasında olamadı? Bu tez, Vâsıt’taki siyasi, sosyal ve iktisadi dinamiklerin ilim ehli üzerindeki etkilerini üç nesil üzerinden incelemekte; şehirdeki ilmî hareketliliği, hoca-talebe ilişkilerini ve bir ilim halkasının sürekliliğini sağlayan ya da sağlayamayan unsurları çözümlemeyi amaçlamaktadır.

Second/ Eighth-century hadith circles of the city of wasit Established in the late 1st/ 7th century by the Umayyad governor of Iraq, al-Ḥajjāj b. Yūsuf, Wāsiṭ was built as a garrison town strategically positioned between the two major centers of learning, Basra and Kufa, reflecting its intended geopolitical significance. With its unique features, the city offers a valuable opportunity to explore compelling questions in early Islamic history. In order to assess Wāsiṭ’s role and significance in the field of ḥadīth studies during the 2nd/ 8th century, it is essential to consider the city’s political, social, and economic conditions. Unlike other cities, the inhabitants of Wāsiṭ did not have direct access to the generation of the Companions (ṣaḥāba) from whom they could learn ḥadīth. Their engagement with the scholarly dynamics of the time was shaped by the city's own socio-intellectual trajectory. This study seeks to answer the following key questions: What kind of scholarly environment did Wāsiṭ offer to its ḥadīth narrators in the 2nd/ 8th century? How did this context affect the formation of study circles (ḥalaqāt)? And why is Wāsiṭ not typically considered among the foremost centers of ḥadīth scholarship of the period? The thesis examines the influence of Wāsiṭ’s political, social, and economic dynamics on its scholarly community across three generations. In doing so, it aims to analyze the nature of scholarly activity in the city, the relationships between scholars and students, and the factors that contributed to the continuity—or lack thereof—of ḥadīth circles.
Second/ Eighth-century hadith circles of the city of wasit
Keywords: 2./ 8. Asır Scholarly Networks; 2nd/ 8th Century; Hadis; Hadis Halkaları; Hadis Tarihi; Hadith; Hadith Circles; Hermeneutics; History of Hadith; Koran; Kur’an-ı Kerim; Tefsirler; Ulema Ağları; Vâsıt; Wasit